Beyond Compliance: A Deep Dive into Improving Sustainability Reporting Quality with LCSA Indicators - Suzana Ostojic; Jana Gerta Backes; Markus Kowalski; Marzia Traverso (Standards)
This study addresses the critical need for improved sustainability reporting in the construction sector, focusing on the integration of Life Cycle Sustainability Assessment (LCSA) indicators to enhance reporting quality and promote standardization. The increasing regulatory pressure from the European Commission, particularly in sustainability reporting, has intensified the demand for corporate transparency. Despite these efforts, many companies still face challenges in implementing robust sustainability performance measures. This research employs a systematic literature review alongside the case studies of three leading German construction companies to critically assess the current reporting practices and explore the integration potential of LCSA indicators. The findings highlight a significant gap between the existing sustainability disclosures and LCSA indicators, with only 7–19% of the assessed indicators being integrated into the current reporting practices. Although some consistency in reporting themes and qualitative disclosures is evident, the misalignment with LCSA indicators underscores the need for further integration of standardized, life cycle-based metrics. This study concludes that collaborative efforts among companies, policymakers, and LCSA researchers are required to bridge this gap, ensuring the adoption of the existing, scientifically robust indicators that enhance the precision, comparability, and transparency of sustainability reporting in the construction sector.